(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
The essay analyses Nuovi racconti italiani, the anthology edited by Antonio Baldini and published by Nuova accademia editrice in 1962. There is no archive of the publishing house, but it was a meritorious enterprise in Milan in the sixties, proposing an idea of universal literature and trying to promote Italian literature abroad. Baldini’s anthology is a completely popular example of this attempt, which nevertheless suffers from a certain delay in developments – just to give an example the Neoavanguardia – of italian narrative in the early sixties.